A Gas Sensor Based on a Single SnO Micro-Disk - Masteghin, Mateus G. [UNESP] (2018)
In this study, individual nanofabricated SnO micro-disks, previously shown to exhibit exceptional sensitivity to NOx, are investigated to further our understanding of gas sensing mechanisms. The SnO disks presenting different areas and thickness were isolated and electrically connected to metallic electrodes aided by a Dual Beam Microscope (SEM/FIB). While single micro-disk devices were found to exhibit short response and recovery times and low power consumption, large interconnected arrays of micro-disks exhibit much higher sensitivity and selectivity. The source of these differences is discussed based on the gas/solid interaction and transport mechanisms, which showed that thickness plays a major role during the gas sensing of single-devices. The calculated Debye length of the SnO disk in presence of NO2 is reported for the first time.